HUBUNGAN SANITASI KANDANG, JARAK KANDANG, KEPADATAN LALAT, JARAK SUMBER AIR BERSIH, DAN PERSONAL HYGIENE DENGAN KEJADIAN DIARE (Studi Pada Peternak Ayam di Kecamatan Benua Kayong Kabupaten Ketapang) - Selviana, Selviana; Arfan, Iskandar; Purwati, Evi (JUMANTIK (Jurnal Mahasiswa dan Peneliti Kesehatan), 2016)
Kecamatan Benua Kayong, Kabupaten Ketapang consists of three villages. Predominantly, the people in these villages work as chicken farmers. As chicken farmers, they are required to directly contact with an environment that has the potential for exposure to the disease, such as diarrhea. Diarrheal diseases are environment-linked diseases that are affected by environmental sanitation, the presence of vectors, and human behavior. A preliminary survey showed that 20% chicken farmers suffered from diarrhea in the last three monts. Factors related to the diarrhea are coop sanitation, coop spacing, fly density, clean water resources, personal hygiene.This study aimed at finding out the correlation of correlation of coop sanitation, coop spacing, fly-density, clean water resources, personal hygiene, and diarrhea case. Using analytic observation, as many as 61 respondents participated in thins study. The statistical test used was chi square test (a=5%)The study revealed that there was correlation of clean water resources and diarrhea cases (p = 0,02, PR=1,480). The variables that didnâ€™t correlate with diarrhea cases were coop sanitation, coop spacing, fly-density, and personal hygiene.From the findings, the chicken farmers in Kecamatan Benua Kayong, Kabupaten Ketapang need to pay more attention on factors deal with diarrhea such as livestock barns environmental management, house cleanliness, personal hygiene, and the selection of healthy drinking water for consumption.Â Keywords : coop, sanitation, fly-density, water resources, personal hygiene, diarrhea cases